Investigating the determinants of e-book adoption. Issue 1 (3rd April 2017) - Hsu, Chia-Lin; Lin, Yu-Hsiang; Chen, Mu-Chen; Chang, Kuo-Chien; Hsieh, Ai-Yun
Abstract : Purpose: The purpose of this paper is to examine the key factors that affect users' adoption of e-books using an extension of the unified theory of acceptance and use of technology (UTAUT) that includes the following factors: environmental concerns, perceived benefits, and benevolence trust. Design/methodology/approach: The authors analyzed survey responses from 343 participants using structural equation modeling to examine the hypothesized relationships in this research model. Findings: The results show that users' adoption of e-books is determined by performance expectancy, effort expectancy, social influence, facilitating conditions, environmental concern, perceived benefit, and benevolence trust. Research limitations/implications: The authors restricted this study to consumers' adoption of e-books. Further studies could examine consumer's adoption of other mediums, such as cutting-edge information technologies. Practical implications: The results suggest that marketers should consider altering their methods of promoting e-books to attract consumers and further affect their usage intention. Originality/value: This study proposes and tests an extended UTAUT model that includes the additional factors of environmental concern, perceived benefit, and benevolence trust in order to examine the influence of these factors on e-book adoption. The findings are particularly useful for assisting managers to increase e-book adoption.